Transisi Freedericksz Pada Kristal Cair Nematik dengan Arah Medan Listrik Eksternal (E) Membentuk Sudut (ï± ) Terhadap Arah Masing-Masing Sumbu Penjajaran Direktor ( nï² ) - , AL JALALI MUHAMMAD ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Freedericksz transition can be understood as a state when the liquid crystal molecules are starting distortion. Freedericksz transition occurs when the electric field (E) is greater than the critical electric field (Ec). The potential when the Freedericksz transition will occur is called the critical potential (Vc). In this study, the formulated of critical field equations (Ec) and critical potential (Vc) by assuming the electric field (E) that applied is forming the slope of angle A against the x-axis (planar condition) in the first case. Then in the second case, the electric field that applied is forming the slope of angle Î¸ against the y-axis (homogeneous conditions) and in the third case, the electric field (E) that applied is forming the z-axis (homeotropik conditions). The liquid crystal molecules are considered rodlike and after the field is applied, the liquid crystal molecules are considered tend to do an alignment with the direction of the electric field (E) applied . The Euler- Lagrange equation is used for the first solution of this research. The strong anchoring Conditions are used as initial and boundary conditions in the final solution of the Diferiansial Ordinary Equations (DOE). In this study, the smallest of the critical potential (Vc) is occurred when electric field applied is forming the slope of 90o to each axis alignment. When the electric field (E) are applied in interval 0o â¤Î¸ â¤ 45 , then the Freedericksz transition is not found. In This case is consistent with the initial assumption that when the liquid crystal molecules are electric field (E) applied, then the liquid crystal molecules tend to do the alignment with the direction of the electric field (E) and was only found when the slope of the electric field applied is at interval 45o <Î¸ â¤ 90o